(untitled) (Research, Society and Development, 2020)
This work had as objective to verify the quality of honey produced in the region of Blumenau/SC - Brazil and possible changes during its storage. For this, analyzes were carried out according to the legislation regarding moisture content, ash, acidity, reducing sugars, apparent sucrose, water insoluble solids, hydroxymethylfurfural, diastase activity, color and lund, fiehe and lugol reaction. The six samples were analyzed shortly after honey harvest and after 10 months of storage. From the obtained results it was verified that 33.33% of the samples presented disagreement with the standards established in the legislation. The parameters that presented the largest number of samples with significant variation along the storage were moisture and diastase activity, 100% and 66,67% respectively, the others had from 16.67% to 50% of the samples with significant variation with the exception of the apparent sucrose, which was the only one that did not have any expressive variation. These analyzes provided greater knowledge of honey produced in the region of Blumenau, thus increasing its added value, in addition to stimulating honey production and guaranteeing the consumer the purchase of a safe and quality product.